2020
DOI: 10.17645/up.v5i1.2528
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualizing Testbed Planning: Urban Planning in the Intersection between Experimental and Public Sector Logics

Abstract: Urban planning is, in many countries, increasingly becoming intertwined with local climate ambitions, investments in urban attractiveness and “smart city” innovation measures. In the intersection between these trends, urban experimentation has developed as a process where actors are granted action space to test innovations in a collaborative setting. One arena for urban experimentation is urban testbeds. Testbeds are sites of urban development, in which experimentation constitutes an integral part of planning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 32 publications
(43 reference statements)
1
15
0
1
Order By: Relevance
“…This suggests that "urban planning in practice pursues different rationalities simultaneously and independently, thereby inevitably contributing to development contradictions and conflicts" (Wolfram, 2018, p. 106), which also seems to apply to the new rationality and associated instruments and objectives of urban experimentation. In Stockholm, for example, this new approach sits-somewhat uncomfortably-next to more traditional planning approaches (Eneqvist & Karvonen, 2021), and a similar development has recently been reported for cities in Denmark and Norway (Berglund-Snodgrass & Mukhtar-Landgren, 2020). These authors explain the mixed feelings of urban planners towards urban experimentation, as reported in this thematic issue by Eneqvist and Karvonen (2021), Räuchle (2021), andWanner et al (2021), as arising from a conflict between institutional logics (beliefs that shape how individuals act).…”
Section: Resultsmentioning
confidence: 63%
“…This suggests that "urban planning in practice pursues different rationalities simultaneously and independently, thereby inevitably contributing to development contradictions and conflicts" (Wolfram, 2018, p. 106), which also seems to apply to the new rationality and associated instruments and objectives of urban experimentation. In Stockholm, for example, this new approach sits-somewhat uncomfortably-next to more traditional planning approaches (Eneqvist & Karvonen, 2021), and a similar development has recently been reported for cities in Denmark and Norway (Berglund-Snodgrass & Mukhtar-Landgren, 2020). These authors explain the mixed feelings of urban planners towards urban experimentation, as reported in this thematic issue by Eneqvist and Karvonen (2021), Räuchle (2021), andWanner et al (2021), as arising from a conflict between institutional logics (beliefs that shape how individuals act).…”
Section: Resultsmentioning
confidence: 63%
“…We began by developing an analytic framework of strategic local government functions inspired by previous research on urban experiments but with a new focus on the broader processes of experimental governance. We then applied this framework to study contemporary experimental governance practices in Stockholm to understand how the municipality performs these functions in practice and, in turn, how this challenges the local government on multiple fronts (Berglund-Snodgrass & Mukhtar-Landgren, 2020). These functions are not new to municipalities but the recent emphasis on urban experimentation reframes and combines them in important ways.…”
Section: Discussionmentioning
confidence: 99%
“…The city, in turn, "becomes a distributed laboratory for testing smart city technologies, especially those utilizing Internet of Things (IoT), run by public and private stakeholders to help solve city challenges and attract investment." (Berglund-Snodgrass & Mukhtar-Landgren, 2020;Coletta et al, 2018, p. 357).…”
Section: Of 10 -Tuitjer and Müllermentioning
confidence: 99%
“…This smart citizen then is the one who has successfully learned how to deal with Information and communication technology (ICT) enhanced urban infrastructures. The city, in turn, “becomes a distributed laboratory for testing smart city technologies, especially those utilizing Internet of Things (IoT), run by public and private stakeholders to help solve city challenges and attract investment.” (Berglund‐Snodgrass & Mukhtar‐Landgren, 2020; Coletta et al., 2018, p. 357).…”
Section: Towards a Research Agenda For Urban Infrastructures As Spacementioning
confidence: 99%